Natural products from Brazilian biodiversity as a source of new models for medicinal chemistry - Bolzani, Vanderlan da Silva [UNESP]; Valli, Marilia [UNESP]; Pivatto, Marcos [UNESP]; Viegas, Claudio (Int Union Pure Applied Chemistry, 2012)
Natural products are the inspiration for many valuable therapeutic agents and attest to biodiversity being a rich source of new molecular structures. Their value as templates for medicinal chemistry remains undisputed, even after the growth of the combinatorial chemistry era. Tropical environments, such as Brazilian biomes, offer a particularly rich potential for biologically active compounds with unique structures and continue to contribute toward modern drug discovery. Our bioprospecting of plant species of the Cerrado and Atlantic Forest biomes has yielded promising bioactive secondary metabolites, and we describe some of these molecules and semisynthetic derivatives as potential acetylcholinesterase (AChE) inhibitors.
Keywords: Brazilian biomes; drug discovery; medicinal chemistry; natural products; tropical biodiversity